STRUCTURE AND DYNAMICS OF THE WATER FILMS CONFINED BETWEEN EDGES OF PYROPHYLLITE: A FIRST PRINCIPLE STUDY - Churakov S.V. (My University, 2007)
Edge sites of clay minerals play a key role for pH dependent sorption of ions from solutions of electrolytes. Pyrophyllite, Al2[Si4O10](OH)2, is an important structural prototype for a variety of 2:1 dioctahedral phyllosilicates but in contrast to the other clays has no permanent structural charge. The structure of thin water films confined between most common edges of 1Tc pyrophyllite: (0 1 0), (1 1 0) and (1 0 0), was analyzed by means of ab initio molecular dynamic simulations. The system setup allowed for a full flexibility of the interfaces and a proton exchange between the edges of pyrophyllite and water molecules in solution. The structure of hydrated surfaces is compared with the recent predictions of static geometry optimizations for edge-vacuum interfaces. All surfaces studied reveal a strong hydrophilic character of edge similar to the hydrated silica surface and the facets of simple layered hydroxides. Spontaneous proton transfer between different surface sites were observed in molecular dynamics simulations of the (0 1 0) interface. The proton bound to the {triple bond, long}Si{single bond}OH site was found to exchange with the {triple bond, long}Al{single bond}OH group by the mechanism {triple bond, long} Si {single bond} OH + {triple bond, long} Al {single bond} OH ↔ {triple bond, long} Si {single bond} O- + {triple bond, long} Al {single bond} OH2+. The direction of the proton transfer agrees with the scale of relative proton affinities for surface sites obtained from the static calculations. Alternatively, the proton attached to the {triple bond, long}Al{single bond}OH2 site exchanges with the {triple bond, long}Al{single bond}OH group. In both reactions, the protons are transferred through the chains of hydrogen bonds formed between water molecules in the solution and the surface sites. The observed mechanisms might be one of the basic schemes for the surface proton diffusion in compacted clays. Kinetics of the proton transfer at edge sites is limited by the rate of rearrangements of the water molecules near interface. © 2006 Elsevier Inc. All rights reserved.